Democracy and federalism in the European Union and the United States : exploring post-national governance - Fabbrini, Sergio (Routledge, 2005)
The European Union - a supranational system with its own institutional characteristics and autonomy - has a structure and functional logic which are more similar to those of the US than those of European nation states. Yet, by and large, the EU and the US tend to be analyzed more as potential geopolitical and economic rivals or allies than compared as institutional peers. By bringing together some of the most influential political scientists and historians to compare the European and American experiences of federalism, Democracy and Federalism in the European Union and the United.